Morinda officinalis oligosaccharides increase serotonin in the brain and ameliorate depression via promoting 5-hydroxytryptophan production in the gut microbiota - Zheng-Wei Zhang; Chun-Sheng Gao; Heng Zhang; Jian Yang; Ya-Ping Wang; Li-Bin Pan; Hang Yu; Chi-Yu He; Hai-Bin Luo; Zhen-Xiong Zhao; Xin-Bo Zhou; Yu-Li Wang; et al. (Elsevier, 2022)
Morinda officinalis oligosaccharides (MOO) are an oral drug approved in China for the treatment of depression in China. However, MOO is hardly absorbed so that their anti-depressant mechanism has not been elucidated. Here, we show that oral MOO acted on tryptophan → 5-hydroxytryptophan (5-HTP) → serotonin (5-HT) metabolic pathway in the gut microbiota. MOO could increase tryptophan hydroxylase levels in the gut microbiota which accelerated 5-HTP production from tryptophan; meanwhile, MOO inhibited 5-hydroxytryptophan decarboxylase activity, thus reduced 5-HT generation, and accumulated 5-HTP. The raised 5-HTP from the gut microbiota was absorbed to the blood, and then passed across the blood-brain barrier to improve 5-HT levels in the brain. Additionally, pentasaccharide, as one of the main components in MOO, exerted the significant anti-depressant effect through a mechanism identical to that of MOO. This study reveals for the first time that MOO can alleviate depression via increasing 5-HTP in the gut microbiota.